Influence of the wavelength on the spatial resolution of pulsed-laser atom probe - Gault, B; Chen, Y; Moody, M; Ohkubo, T; Hono, K; Ringer, S (2011)
Modern atom probes typically incorporate an ultrafast pulsed-laser source with wavelength ranging from infrared (IR) to ultraviolet (UV) depending on the specific instrument. In order to estimate the influence of the wavelength on the accuracy of the technique, the achievable in-depth spatial resolution has been measured for atom probe analyses of the same pure W specimen using three different wavelengths and across a range of laser pulse energies. UV illumination is shown to yield superior spatial resolution to both IR and visible (green) wavelengths. We propose that this improvement relates to a faster decay of temperature enabled by light absorption confined to the near apex region. © 2011 American Institute of Physics.